Air-stable plasmonic bubbles as a versatile three-dimensional surface-enhanced Raman scattering platform for bi-directional gas sensing. Issue 47 (25th May 2022) - Leong, Yong Xiang; Koh, Charlynn Sher Lin; Phan-Quang, Gia Chuong; Tan, Emily Xi; Wong, Zhao Cai; Yew, Wee Liang; Lim, Bao Ying Natalie; Han, Xuemei; Ling, Xing Yi
Abstract : 'Plasmonic bubbles' as a versatile, air-stable, centimetre-sized 3D SERS platform with bi-directional gas sensing capabilities. Abstract : Harnessing large hotspot volumes is key for enhanced gas-phase surface-enhanced Raman scattering (SERS) sensing. Herein, we introduce versatile, air-stable 3D 'Plasmonic bubbles' with bi-directional sensing capabilities. Our Plasmonic bubbles are robust, afford strong and homogenous SERS signals, and can swiftly detect both encapsulated and surrounding 4-methylbenzenethiol vapors.